Prevalence and Review of Pathological Anatomy of Gestational Choriocarcinoma in Ibadan (2022)
Objectives: Gestational choriocarcinoma (GCC) is a highly malignant epithelial tumor arising from the trophoblast of any type of gestational event, most often a complete hydatidiform mole. Choriocarcinoma is the most aggressive form of gestational trophoblastic neoplasia due to its rapid growth and metastatic potential. This study reviewed all cases of GCC seen at the University College Hospital, Ibadan. Methods: This was a 20-year retrospective hospital-based study designed to review all histologically diagnosed cases of choriocarcinoma registered at the Department of Pathology, University College Hospital (UCH), Ibadan, Nigeria, from 1st January 1997 to 31st December 2016. Clinicopathological data were extracted from the departmental surgical day book, ward register, Department of Medical Records, and Cancer Registry. The data were analyzed using the Statistical Package for Social Sciences (SPSS), version 22. Results were presented in tables, relative frequencies, and group percentages. Results: One hundred and eighty-three cases of gestational trophoblastic disease were histologically diagnosed within the study period, of which 36 cases were GCC, accounting for 19.7%. Of all the cases, 55.6% were received as endometrial biopsies, 33.3% as hysterectomy specimens, 8.3% as cervical biopsies, and 2.8% as an anterior vaginal wall mass. Choriocarcinoma occurred in the age range of 20 to 50 years, with the majority of cases occurring in the third decade of life. Conclusion: Gestational choriocarcinoma remains the most common form of gestational trophoblastic neoplasia in our environment. Awareness of this tumor, along with a high index of suspicion, is essential for accurate diagnosis and effective patient management.